Editorial - Fernández Arata, Manuel (2017)
This issue of Liberabit, Peruvian Journal of Psychology, comprises articles covering a range of topics mentioned below. The original articles section begins with a report by Pedro Gil-Monte, Sara Viotti and Daniela Coverso of the psychometric properties of the Questionnaire for Assessing Workplace Burnout Syndrome (CESQT) in Italian health professionals. This study contributes to demonstrate the psychometric validity of the questionnaire at international level, regardless of the gender, thus consolidating its cross-cultural nature...